Sapphire Series 1: Activity Book for English Language Support Programmes - Norhana Abdullah; Juliana Niza Ismail Adnan (Universiti Sains Islam Malaysia, 2022)
Sapphire is ideal for English Language learners by providing engaging, learner-centered task-based activities. Designed to introduce English language learning to average learners, this activity book opens the door to a wider social and academic experiences to first year university student. It assist in developing the ability to use English confidently and effectively to meet social and academic demands.